Who chooses "healthy" meals? An analysis of lunchtime meal quality in a workplace cafeteria - Sally L. Bullock; Hilary M. Winthrop; Derek Hales; Feng-Chang Lin; Yumei Yang; Alice S. Ammerman; Anthony J. Viera (BMC, 2024)
Abstract Background The workplace can play an important role in shaping the eating behaviors of U.S. adults. Unfortunately, foods obtained in the workplace tend to be low in nutritional quality. Questions remain about the best way to approach the promotion of healthy food purchases among employees and to what extent health promotion activities should be tailored to the demographic characteristics of the employees. The purpose of this study was to (1) assess the nutritional quality of lunchtime meal purchases by employees in cafeterias of a large organization, (2) examine associations between lunchtime meal quality selection and the demographic characteristics of employees, and (3) determine the healthfulness of foods and beverages offered in the cafeterias of this organization. Methods A cross-sectional analysis was conducted using secondary data from a food labeling study implemented in three worksite cafeterias. Demographic data was collected via surveys and meal data was collected using a photo capture system for 378 participants. The Healthy Eating Index 2015 (HEI-2015) was used to determine meal quality and a total score for the menu of options available in the cafeterias during the study period. Summary statistics were generated, and the analysis of variance (ANOVA) was used to compare the HEI-2015 scores between groups. Results The mean HEI-2015 total score for the menu items offered (n = 1,229) in the cafeteria during the study period was 63.1 (SD = 1.83). The mean HEI-2015 score for individual lunchtime meal observations (n = 378) was 47.1 (SD = 6.8). In general, HEI-2015 total scores were higher for non-smokers, individuals who self-identified as Asian, had higher physical activity levels, scored higher on numeracy and literacy assessments, and reported higher education levels, incomes, and health status. Conclusions The overall HEI-2015 scores indicate that the menu of options offered in the cafeterias and individual meal selections did not align with the Dietary Guidelines for Americans, and there were significant associations between average lunchtime meal quality scores and several demographic characteristics. These results suggest that healthy eating promotion activities in workplaces may need to be tailored to the demographic characteristics of the employees, and efforts to improve the food environment in the workplace could improve meal quality for all employees.